Continuous ⁎-K-G-Frame in Hilbert C⁎-Modules. (31st July 2019) - Rossafi, Mohamed; Touri, Abdeslam; Labrigui, Hatim; Akhlidj, Abdellatif
Abstract : Frame theory is exciting and dynamic with applications to a wide variety of areas in mathematics and engineering. In this paper, we introduce the concept of Continuous ⁎-K-g-frame in Hilbert C ⁎ -Modules and we give some properties.